(untitled) (City: History, Culture, Society, 2017)
Irina Scubi managed to take a fresh look at certain social and cultural problems related to the development of trade at this time. The researcher was able to show the interrelationships of various types of trade the time of the city, the place of the average trader and authorities in changing 20th years of the twentieth century. It should be noted separately that the researchers managed to combine the methods of economic and historical research. Although this is a difficult task, since studying the issues of economic development, trade, operating statistics, Turning to an array of economic works is difficult to not use the toolkit of economic research.